2020
DOI: 10.3390/nano10091640
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Behaviors of Ag2S Nanosheets: An in Situ High-Pressure X-Ray Diffraction Research

Abstract: An in situ high-pressure X-ray diffraction study was performed on Ag2S nanosheets, with an average lateral size of 29 nm and a relatively thin thickness. Based on the experimental data, we demonstrated that under high pressure, the samples experienced two different high-pressure structural phase transitions up to 29.4 GPa: from monoclinic P21/n structure (phase I, α-Ag2S) to orthorhombic P212121 structure (phase II) at 8.9 GPa and then to monoclinic P21/n structure (phase III) at 12.4 GPa. The critical phase t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…43(6) . This particular morph was observed for the tens of nanometer-size overlayers [23] and quantum dots [24] of similar characteristic sizes. Moreover, yet another monoclinic form of three-dimensional Ag 2 S was identified in Ref.…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations
“…43(6) . This particular morph was observed for the tens of nanometer-size overlayers [23] and quantum dots [24] of similar characteristic sizes. Moreover, yet another monoclinic form of three-dimensional Ag 2 S was identified in Ref.…”
Section: Introductionmentioning
confidence: 58%
“…[22], it was shown that the nanocrystalline form of Ag 2 S has space group P2 1 /c ( Z = 4), and the following unit cell parameters were reported: a = 4.234(3) Å; b = 6.949(3) Å; c = 9.549(5) Å; and β = 125.43(6)°. This particular morph was observed for the tens of nanometer‐size overlayers [ 23 ] and quantum dots [ 24 ] of similar characteristic sizes. Moreover, yet another monoclinic form of three‐dimensional Ag 2 S was identified in Ref.…”
Section: Introductionmentioning
confidence: 69%
See 2 more Smart Citations
“…Indeed, Ag 2 S QDs display presence of many strong diffraction peaks orientation along (110), (200), (211), (220), and (310) plane indicate the polycrystalline nature of films, which has been belong to the cubic phase, (JCPDS-00-001-1151). This can be explaining since Ag 2 S is stable in a monoclinic structure at room temperature, but suffers a thermo-induced phase shift into a cubic structure at 450 K 50 . Silver ions are randomly dispersed across the interstitial sites of a sulphur lattice in this high-temperature structure, resulting in a favourable ionic conductivity owing to the quantum effect of particle size.…”
Section: Resultsmentioning
confidence: 99%